PRESTASI KERJA BERBASIS KEDISIPLINAN, KEMAMPUAN KERJA, DAN PROFESIONALISME PEGAWAI NEGERI SIPIL DI SATUAN KERJA INSTANSI XYZ - Fadhilah Agustya,; Daniel Ong Kim Kui,; Rudy Pramono, (Journal of Innovation Research and Knowledge, 2024)
Human resources are the main asset in an organization because their contribution plays important role that can reflect the organization's achievements. In this way, an HR management process is needed so that organizational goals can be achieved, supported by a high level of work performance. In this research, the authors examine whether discipline, work ability and professionalism can influence work performance. This research is based on the author's curiosity about what factors influence work performance in government organizations, especially one of the work units at the XYZ Department which has 228 Civil Servants (PNS). This work unit is dominated by employees with relatively long working period and the phenomenon of declining work performance that occurred in first and second period in 2021 that was discovered. It is expected that this research will find factors that can significantly influence work performance. Questionnaires were used in the data collection process, and 163 respondents were obtained for the measurement process using SmartPLS software. The results show that discipline and work ability can have a positive and significant influence on increasing work performance. Meanwhile, professionalism does not show positive and significant influence on the work performance of civil servants as research subjects.